Synthesis, characterization, kinetic and thermodynamic parameters evaluation from TG-DTA analysis of Cu(II), Co(II) and Mn(II) complexes with two phenol Schiff bases - Abbas, Hayat Hamza (European Journal of Chemistry, 2016)
Complexes of Cu(II), Co(II) and Mn(II) with two Schiff base ligands {[(2-carboxyphenyl)imino]methyl} phenol (HLA) and {[(2-hydroxyphenyl)imino]methyl} phenol (HLB) were synthesized and characterized by FT-IR, UV-Visible, 1H NMR spectroscopy and elemental analysis. All the synthesized complexes have been evaluated for their thermal degradation studies using TG-DTA analytical methods in static air. Thermodynamic and kinetic parameters were evaluated from the TG-DTA curves using Arrhenius equation.